Morality Going Concrete: A Medieval Mystery With Dancing Elephants - Taylor, Scott (Organizational Aesthetics, 2012)
"Write about 500 words about the play. It's not a review in the way that you review a journal submission; if you don't like the play, don't write anything." This is a bit unusual as guidance from a journal editor - but then the journal is unusual, the way that organization and aesthetics interact is not normal (in the sense that it's different from the b-school norm, how organization and (social) sciences speak to each other), and this isn't the kind of thing you normally read in a scholarly journal.